Diseño y construcción de un prototipo de persiana con ajuste automático de iluminación para las aulas de bloque 3 de la FEIRNNR - Carreño Ordóñez, Jimmy Paúl (2023)
Light is an electromagnetic wave that stimulates the retina of the human eye to perceive color; as this resource is highly efficient with respect to color rendering. Therefore, the Universidad Nacional de Loja by promoting innovation to solve social problems, in this research a prototype of automatic blinds was implemented to regulate the level of brightness in the classrooms of FEIRNNR; which presents IoT technology focused on improving the student ergonomics. For this purpose, the lighting averages inside and outside the classroom were calculated, resulting in 1531.21 lx in the interior part and 43540.6464 lx of lighting in the exterior part, obtaining a daylight factor of 3.56% and lighting levels higher than those required by the regulations. Therefore, a mobile application called PerIot was designed, capable of controlling the movement of a blind via web, manually or automatically, in the same way, it can be done physically from the control panel designed; allowing greater versatility with respect to other control mechanisms, in the same way, its cost makes the prototype competitive, since in the local market there aren’t control systems of this type. In addition, the prototype automatically allows to take advantage of the levels of natural light that exists outside, this being a preamble to energy efficiency in the classroom. 3 Keywords: IoT, rolling shutter, Firebase, Android Studio, lighting.